Design and Evaluation of a Virtual Reality Learning Game for Interior Design Styles - Mikhael Ming Khosasih; Andre; Timothy Wahyudi Santoso (SMATIKA JURNAL : STIKI Informatika Jurnal, 2026)
Public understanding of interior design styles is still limited because conventional two-dimensional (2D) media cannot adequately represent spatial depth, perspective, and the distinguishing characteristics of each style. This limitation often leads to misconceptions when identifying interior design concepts and elements. Therefore, this study aims to design and evaluate a Virtual Reality (VR)-based learning game as an immersive medium for introducing interior design styles. The system was developed using the Mechanics, Dynamics, and Aesthetics (MDA) framework and implemented in Unity with the XR Interaction Toolkit for the Meta Quest 2 platform. The application includes five interior design styles—modern, minimalist, industrial, natural, and rustic—and provides interactive tasks that allow users to explore, manipulate, and apply interior elements in a virtual environment. To evaluate its effectiveness, a pretest–posttest experiment was conducted with 30 participants. The results show that the average score increased from 31.25% in the pretest to 56.25% in the posttest, indicating an improvement of 25 percentage points. A paired-samples t-test also showed a statistically significant improvement, with p < 0.001. These findings suggest that the proposed VR learning game has the potential to improve users’ understanding of interior design styles.